Cognitive instruments of the translation analysis of L. Carroll’s language game - Богуславська, Людмила Анатоліївна (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2018)
The article outlines the principles of a cognitive analysis of English-Ukrainian translations of L. Carroll’s language game which applies the apparatus of the conceptual blending theory to the analysis of the English-Ukrainian translations of nonsense words from L. Carroll’s poem «Hunting of the Snark». The conceptual blending theory explains cognitive mechanisms which underpin a communicatively successful translation of nonsense words. Such nonsense words activate in the mind of an interpreter two input mental spaces containing semantically incongruent structure, representing associations a nonsense word has in the world of reality and in the fantastic world of L. Carroll’s poem. Projection of the structure from the input spaces in the blend and realising this incongruity while unpacking the blend sanctions recognition of the humorous stimulus. In the process of backward projection to the input mental spaces this incongruity is reassessed against the background of encyclopaedic knowledge and broader linguistic context and gives rise to various interpretations. A communicatively successful translation of nonsense words must render semantic incongruity of the original which opens the possibility of such interpretations. Realisation of this possibility depends on the cognitive and emotional experience of the reader. Applying the instrumental notions of the conceptual blending theory in translation analysis builds the algorithm of analysis to avoid subjectivity.